If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + 6) + (-6x + 5) = 0 Reorder the terms: (6 + 5x) + (-6x + 5) = 0 Remove parenthesis around (6 + 5x) 6 + 5x + (-6x + 5) = 0 Reorder the terms: 6 + 5x + (5 + -6x) = 0 Remove parenthesis around (5 + -6x) 6 + 5x + 5 + -6x = 0 Reorder the terms: 6 + 5 + 5x + -6x = 0 Combine like terms: 6 + 5 = 11 11 + 5x + -6x = 0 Combine like terms: 5x + -6x = -1x 11 + -1x = 0 Solving 11 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -1x = 0 + -11 Combine like terms: 11 + -11 = 0 0 + -1x = 0 + -11 -1x = 0 + -11 Combine like terms: 0 + -11 = -11 -1x = -11 Divide each side by '-1'. x = 11 Simplifying x = 11
| 20x+x*x*x+9x*x=0 | | 32x+7=15 | | 7+x+(4x+7)= | | 2x+4=16-x | | 4w=-1 | | 5x=6y | | 2x+3=147 | | 9x^4+4x^2+1=0 | | 10x^2-4X+12=Y | | 34-5x=4x+24 | | x^2-4x=2 | | x^2-605x+1206=0 | | 8-7x=98-42x | | 2x+3-4=3x+6+6 | | x^10*e^6= | | -9x^3+18x^2-12x-8= | | 2*x*x-8=42 | | 2*x=40 | | 21=v(v-4) | | 2xx-8=40 | | 3x^2+7x+13=11 | | 2x-3=64 | | y-.8y=74 | | -5+12=17x-3-16x | | -5x*-3+8= | | 7x+1=-20 | | -5x*3+8= | | -3(x+8)-43=2-42 | | solvex^2=-7x-7 | | 22-x=2x+10 | | 22-x=2(x-5) | | -4-7=-9+x |